2012
DOI: 10.1007/s00367-012-0292-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermal anomalies associated with shallow gas hydrates in the K-2 mud volcano, Lake Baikal

Abstract: Thermal measurements and hydrate mapping in the vicinity of the K-2 mud volcano in Lake Baikal have revealed a particular type of association of thermal anomalies (29-121 mW m(-2)) near hydrate-forming layers. Detailed coring within K-2 showed that hydrates are restricted to two distinct zones at sub-bottom depths exceeding 70-300 cm. Temperature data from stations with hydrate recovery and degassing features all display low thermal gradients. Otherwise, the thermal gradients within the mud volcano are general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…More than a year (431 days) of monitoring at Håkon Mosby MV revealed pulses of hotter subsurface fluids accompanied by small eruptions which represent similar events to those observed onshore during the dormancy of MVs (Feseker et al, 2014). Campaigns completed at the K-2 MV in Lake Baikal showed the presence of gas hydrates and revealed the presence of low and high thermal anomalies that are interpreted to result from a shallow fluid circulation that interacts with a dynamic hydrate system just below (Poort et al, 2012).…”
Section: Temperaturementioning
confidence: 66%
“…More than a year (431 days) of monitoring at Håkon Mosby MV revealed pulses of hotter subsurface fluids accompanied by small eruptions which represent similar events to those observed onshore during the dormancy of MVs (Feseker et al, 2014). Campaigns completed at the K-2 MV in Lake Baikal showed the presence of gas hydrates and revealed the presence of low and high thermal anomalies that are interpreted to result from a shallow fluid circulation that interacts with a dynamic hydrate system just below (Poort et al, 2012).…”
Section: Temperaturementioning
confidence: 66%
“…Among twenty hydrate-bound cores in the Kedr area, four cores contained sI only, seven cores had sII only, and seven cores showed sII at the upper layer and sI at the lower layer, as observed at the Kukuy K-2 MV 13,16,17 . Furthermore, in the cores 2015St1GC15 and 2016St18GC2, gas hydrate structure had sI at the upper and lower layer, and sII at the middle layer.…”
Section: Discussion Origin Of Hydrate-bound Hydrocarbonsmentioning
confidence: 68%
“…Such a composition of thermogenic gas is, therefore, considered to be supplied from a deep sediment layer, forming sI gas hydrates composed of mainly C 1 and C 2 11,12 in the lake floor sediment. In the cases where sI gas hydrates plug and block migration pathways, upward fluid flow becomes more focused in other areas 16 . Once gas supply stops locally, gas hydrates begin to decompose, with the gas dissolving into gas-poor sediment pore water.…”
Section: Discussion Origin Of Hydrate-bound Hydrocarbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that the formation of gas hydrate will reduce the permeability of sediments to different degrees and will change the direction of fluid leakage. For example, one report stated that during the process of fluid migration, gas hydrate will block some of the migration pathways and lead to more concentrated fluid migration in the region [70]. Another study revealed that the lateral migration of methane-containing fluid was driven by the formation of gas hydrate and the blockage of pore space at the seepage center [71].…”
Section: Cold Seep Formation and Evolution Models In The Studymentioning
confidence: 99%